Composition and Diversity of Soil Microbial Community Associated With Land Use Types in the Agro–Pastoral Area in the Upper Yellow River Basin - Liu, Shiliang; Sun, Yongxiu; Shi, Fangning; Liu, Yixuan; Wang, Fangfang; Dong, Shikui; Li, Mingqi (Frontiers in Plant Science, 2022)
Soil microorganisms are sensitive to their living microenvironment, and their community structure and function will change with the environmental conditions. In the agro-pastoral area on the Qinghai-Tibet Plateau, revealing the diversity of soil microbial communities and its response to different soil physicochemical properties and environmental factors are important for ecosystem management. The microbial (Bacteria and Archaea) community composition and diversity under different land use types (cultivated land, grazing grassland and planted forest) were analyzed by 16S rRNA (V4 region) method in a typical agro-pastoral region in the upper Yellow River basin. Also, soil nutrients were studied and correlated with the microbial community. The results showed that soil nutrient contents in grassland were low, but the available nutrients were relatively high. There was great spatial variability under different distances to the river. The microbial community diversity was lower in the grassland than cultivated land and forest land closer to the river. For all land uses, the dominant phyla of soil microorganisms included Proteobacteria, Actinobacteria, and Bacteroidetes, while the abundance of Clostridia was significantly higher than that of other groups, indicating that Clostridia dominated the Firmicutes and affected soil microbial community composition. Linear discriminant analysis effect size (LefSe) analysis showed different biomarkers were more abundant in grassland than other land use types, suggesting that the structure and diversity of soil microorganisms in grassland were significantly different compared with cultivated land and forest land. Distance-based redundancy analysis (db-RDA) results showed that the total phosphorus (TP) and Ca were the key environmental factors affecting the diversity and abundance of soil microbial community in cultivated land and forestland, respectively. However, microbial diversity in grassland was more related to spatial distance of the river. These results provided a theoretical basis for the changes in the composition, structure and function of soil microbial communities in agro-pastoral areas.